Kiasu and creativity in Singapore: An empirical test of the situated dynamics framework - CHENG, Chi-Ying (Institutional Knowledge at Singapore Management University, 2017)
This article investigates how Singaporeans' creativity is influenced by Kiasu, an indigenous construct corresponding to fear of losing out. We examine the impact of Kiasu on creativity, both as a personal value and a shared cultural norm in four studies. Study 1 showed that Singaporeans' Kiasu value endorsement predicts lower individual creativity. Study 2 demonstrated that this negative relationship is mediated by a self-regulatory focus on prevention. Study 3 further showed the impact of Kiasu as a personal value and a cultural norm by finding a significant three-way interaction effect of Kiasu prime, personal Kiasu value endorsement, and need for cognitive closure on participants' creativity. Study 4 addressed the Singaporean paradox and found that Singaporeans exhibit higher creativity when primed with their multi-ethnic culture than under control conditions. However, those who associated Singapore with Kiasu lost this advantage. These findings support the situated dynamics framework of cultural influence on behavior such that values, norms, and situational cues play a role in producing a cultural pattern of creative performance. This research also has implications for how to incubate creative performance in Asian countries.